2009
DOI: 10.1002/mabi.200900253
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Polyphosphoesters: From Controlled Synthesis to Biomedical Applications

Abstract: Polyphosphoesters (PPEs) with repeating phosphoester bonds in the backbone are structurally versatile, biocompatible, and biodegradable through hydrolysis as well as enzymatic digestion under physiological conditions. They are appealing for biological applications because of their potential functionality, biocompatibility, and similarity to biomacromolecules such as nucleic acids. The expanding scope of PPEs in materials science, especially as biomaterials, is described in this review. We mainly focus on contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
155
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(157 citation statements)
references
References 93 publications
0
155
0
Order By: Relevance
“…They found that as the temperature was increased above the LCST the micelles became more hydrophobic and formed aggregates in a reversible way [163,164]. The micelles were found to be both biodegradable and non cytotoxic showing a promising drug delivery vector [163,164].…”
Section: Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that as the temperature was increased above the LCST the micelles became more hydrophobic and formed aggregates in a reversible way [163,164]. The micelles were found to be both biodegradable and non cytotoxic showing a promising drug delivery vector [163,164].…”
Section: Particlesmentioning
confidence: 99%
“…Jun Wang et al have produced a series of thermoresponsive micellar nanoparticles from PVCL and polyphosphoester and examined their cell change in size with temperature [163,164]. They found that as the temperature was increased above the LCST the micelles became more hydrophobic and formed aggregates in a reversible way [163,164].…”
Section: Particlesmentioning
confidence: 99%
“…[27][28][29] As previously reported, polyphosphoesters featuring a linear molecular structure can be synthesized through the ringopening polymerization reaction of EEP in tetrahydrofuran, utilizing ROH or RNH 2 as the co-initiator, and Sn(Oct) 2 as the catalyst. 30 In this work, the PAEEP-PLLA copolymer was synthesized as illustrated in Figure 2.…”
Section: Results and Discussion Synthesis Of Paeep-plla Copolymermentioning
confidence: 86%
“…The pentavalency of phosphorous enables covalent linkages to prepare prodrugs of this polymer (1). PPE and its composites have been used in gene delivery, drug delivery, and in tissue engineering applications (31). PPE and its copolymers can form films, gels, micelles, and particles (1).…”
Section: Poly(α-hydroxy Acids)mentioning
confidence: 99%